KONTRIBUSI PENDAPATAN INDUSTRI RUMAH PANGGUNG TERHADAP PENDAPATAN RUMAH TANGGA MASYARAKAT DI DESA WOLOAN SATU UTARA KEC. TOMOHON BARAT - Yosua Kalangi . Kalangi; Paulus A. Pangemanan; Juliana R. Mandei; Caroline B. D. Pakasi (Sam Ratulangi University, 2015)
This study aims to determine the contribution of revenue from industrial houses on stilts on household income. This research was conducted for four months starting in February 2015 to May 2015 in the village of Woloan One North district. Tomohon West. The population in this study was people who became workers in home industries stage. Of the population of 30 samples has taken using simple random sampling method. In this study, the data used are primary and secondary data obtained from the relevant agencies, namely the Village district office Woloan One District Tomohon North West. The data is processed using descriptive analysis. The results showed that the contribution of revenue from the industry is a stilt house by 84% and are potentially in employment. The amount of revenue contribution from home industry is very influential stage in household income, while contributions outside the home industry are less influential stage in household income. For the second job in industry stilt house can be made in the main work as a source of household income communities Woloan One Village North.